The pacified city seen from the drone - Beyaert-Geslin, Anne (E|C, 2021)
The images produced by the impersonal eye of a drone introduce a new perspective in the genre of aerial imagery. After having marked their place in a genealogy, the article characterizes them by the criteria of height, mobility and disengagement to define their unique relation to space. It thus describes an effect of naturalization. These images are characterized by a completely paradoxical instantiation which delivers banal representations in the sense that they show universes transformed by human presence, familiar landscapes where we could go, although they are seen from the height of the bird. It thus offers a peaceful and irenic vision of the city.